THE ROLE OF MARKETING AND CONSUMER PSYCHOLOGICAL FACTORS ON PURCHASING DECISIONS TO INCREASE SALES (Study Case On Small And Medium Business Entrepreneur On Graha Permata Indah Residence) - Muhammad Rapita Kun Panuluh; I Dewa Made Yuda Mahendra; Ivan Faris Arifin (Jurnal Ekonomi, 2022)
In a business, marketing strategies are necessary to increase sales. Therefore, company management is needed in order to determine the marketing strategy that will be used in the future appropriately. Marketing strategies can be done through massive promotions on social media, applying tantalising discounts, working with public figures and influencers for a wider target audience, and through newsletters. However, apart from the above dominant factors that can be optimised in marketing strategies, there is another determining factor that should not be underestimated. The factor is the psychology of marketing. Psychology of Marketing is one of the sciences in the marketing world to understand the psychology of customers when they visit the products offered until the final decision to purchase the product. It can applied to social media marketing strategies, website promotions, or others. By applying marketing psychology, marketers can more easily understand the habits, traits, tendencies, and other things that customers like before they finally buy a product. The aims of this research were: (1) To find out how marketing psychology influences consumer psychological factor. (2) To find out how consumer psychology affects purchasing decisions (3) To find out how psychological marketing strategy affect purchasing decisions directly. (4) To find out how the influence of marketing psychology on purchase decisions are made using consumer psychology as an intermediary variable. Data were collected by distributing questionnaires directly to customers and through the Google Forms model with Up to 112 people can respond. Structural Equation Modeling (SEM) analysis was used to test measurement and structural models through IBM SPSS AMOS v.24. This research results suggest that all hypotheses are accepted which proves that all hypotheses make a significant impact with positive value on each other.